Human Capital in the Enterprise – A Theoretical Approach - Drobny, Paweł (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
Contemporary theories of economics are focused on human qualities as an autonomous production factor. The consequence of this is neglecting to describe the relationship between human capital and human beings, who are the “bearer” of the capital, and the formation of human capital. As a production factor, human capital may make sense only in the context of a specific company, because it creates the conditions in which the potential of human qualities is recognised and used.The thesis pursued in the article is as follows: human qualities, especially knowledge and skills, are an integral part of a person. This means that they are involved in each experience a human has as both its cause and its effect. It is therefore a mistake to analyse their economic importance in isolation from the whole complexity of the human.The first part of the article presents the approach of contemporary theories of economics to the problem of human capital in enterprise. The second part examines the new conceptualisation of the role human qualities play in enterprise. This conceptualisation can be described as “personalist economics”.